1995
DOI: 10.1016/s0022-5223(95)70091-9
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and intraoperative ultrasonographic examination as an aid in lung cancer operations

Abstract: To assess the extent of tumor invasion in lung cancer, my colleagues and I routinely use preoperative transesophageal ultrasonic endoscopy and intraoperative ultrasonography in addition to preoperative roentgenography, computed tomographic scanning, and other standard procedures. Both transesophageal ultrasonic endoscopy and intraoperative ultrasonography allow for a real-time assessment of the extent to which the lung cancer has invaded adjacent organs and are useful in determining the operability and safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
2

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 12 publications
0
10
0
2
Order By: Relevance
“…Ultrasonography is widely used as a diagnostic tool in various clinical fields, such as percutaneous echoes [6], echoes during surgery [7 -11] and transbronchial echoes. However, only a few researchers have reported that ultrasonography can identify peripheral pulmonary nodules [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonography is widely used as a diagnostic tool in various clinical fields, such as percutaneous echoes [6], echoes during surgery [7 -11] and transbronchial echoes. However, only a few researchers have reported that ultrasonography can identify peripheral pulmonary nodules [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Importantly, this tech-nique has now made it possible both to detect small nodules in the lung and to evaluate whether the lines of resection will achieve the required margins for solid lung nodules. 3,4,[6][7][8][9][10][11][12][13][14][15] Although the utility of IU for the management of GGO has remained unclear, we hypothesized that this procedure would enable the identification of small GGO lesions deep in the parenchyma and could serve as a guide in finding the appropriate margin in a deflated lung.…”
mentioning
confidence: 99%
“…would be necessary. Therefore our investigations so far can not confirm the results and positive assessme nt made by Totsumum, who evaluated tum or invasion with a sensitivity of 97% (11). Given an increase in sound frequency for intraoperativelyapplicable probes such resu lts will of course be possible in the future.…”
Section: Discussionmentioning
confidence: 67%